دلالات التراكيب الاسمية في القرآن الكريم سورة "المؤمنون" أنموذجا - بن سعدية, خليفة; عيساني, عبد القادر; بن ناهيه, عبد المالك (جامعة الوادي - University of Eloued, 2023)
Summary Our memorandum, which is tagged with the title: "Semantics of Nominal Structures in the Holy Qur'an, Surat Al-Mu'minun as a Model", deals with the relationship of the semantics of nominal structures to the general interpretation of the Surah, by linking these connotations to the interpretation of the Surah. Then search for their connotations, trying to simplify and explain the concepts, in the theoretical chapter, as these structures multiplied between nominal sentences that generally indicate stability and permanence, and additional and descriptive structures that indicate in their entirety specification, clarification, and a statement of the characteristic of the described, while we counted the nominal structures - with an indication Its implications and the changes that occurred to it, as well as the implications of those changes - in the applied chapter. Through this study, we have reached: - That there is a close relationship between the semantics of nominal structures and the general interpretation of the surah in terms of meaning. - That the nominal structures carry general and fixed connotations did not prevent them from giving them special connotations through the context. It should be noted that this study can be in-depth in the future